Visibility of scientific production of University Hospital "General Calixto García" according to Scopus. 1972-2014 - Alberto Juan Dorta Contreras (Universidad de Ciencias Médicas de La Habana, 2015)
Introduction: The University Hospital "General Calixto García" is a symbol of health care since revolution´s triumph. Scopus, the biggest papers database of the world with external peer review let to mark off, analyze and visualize researches. Objective: The aim of this paper is characterize the visibility of the scientific productivity by this hospital during 1972 -2014 according to Scopus database. Material and Methods: Sciences metric descriptive study was done using published articles indexed in the database Scopus and authors belonging to the University Hospital "General Calixto García Iñiguez". Results: The scientific productivity was 6 papers per year. The most representative speciality was medicine and surgery. 24% was published in international journals. Among the most productive authors, the first two places were occupied by two women. Among the most cited papers, eight was published in English and all of them in international journals. The first papers were cited in 1973 and were corresponding to surgery. Conclusions: The conclusion is that the visibility of the scientific production is below the professional potency of this health centre because there are some scientific production results that are not included in journals indexed by Scopus database.  Key words: scientific production, visibility, hospital, science, health.